Transcranial Magnetic Resonance Imaging-Guided Focused Ultrasound with a 1.5 Tesla Scanner: A Prospective Intraindividual Comparison Study of Intraoperative Imaging - Cesare Gagliardo (Brain Sciences, 2021)
Background: High-quality intraoperative imaging is needed for optimal monitoring of patients undergoing transcranial MR-guided Focused Ultrasound (tcMRgFUS) thalamotomy. In this paper, we compare the intraoperative imaging obtained with dedicated FUS-Head coil and standard body radiofrequency coil in tcMRgFUS thalamotomy using 1.5-T MR scanner. Methods: This prospective study included adult patients undergoing tcMRgFUS for treatment of essential tremor. Intraoperative T2-weighted FRFSE sequences were acquired after the last high-energy sonication using a dedicated two-channel FUS-Head (2ch-FUS) coil and body radiofrequency (body-RF) coil. Postoperative follow-ups were performed at 48 h using an eight-channel phased-array (8ch-HEAD) coil. Two readers independently assessed the signal-to-noise ratio (SNR) and evaluated the presence of concentric lesional zones (zone I, II and III). Intraindividual differences in SNR and lesional findings were compared using the Wilcoxon signed rank sum test and McNemar test. Results: Eight patients underwent tcMRgFUS thalamotomy. Intraoperative T2-weighted FRFSE images acquired using the 2ch-FUS coil demonstrated significantly higher SNR (R1 median SNR: 10.54; R2: 9.52) compared to the body-RF coil (R1: 2.96, p < 0.001; R2: 2.99, p < 0.001). The SNR was lower compared to the 48-h follow-up (p < 0.001 for both readers). Intraoperative zone I and zone II were more commonly visualized using the 2ch-FUS coil (R1, p = 0.031 and p = 0.008, R2, p = 0.016, p = 0.008), without significant differences with 48-h follow-up (p ≥ 0.063). The inter-reader agreement was almost perfect for both SNR (ICC: 0.85) and lesional findings (k: 0.82–0.91). Conclusions: In the study population, the dedicated 2ch-FUS coil significantly improved the SNR and visualization of lesional zones on intraoperative imaging during tcMRgFUS performed with a 1.5-T MR scanner.